Performance of an anaerobic membrane bioreactor for pharmaceutical wastewater treatment - Svojitka, Jan; Dvořák, Lukáš; Studer, Martin; Straub, Jürg Oliver; Frömelt, Heinz; Wintgens, Thomas (Bioresource technology, 2017)
Anaerobic treatment of wastewater and waste organic solvents originating from the pharmaceutical and chemical industries was tested in a pilot anaerobic membrane bioreactor, which was operated for 580days under different operational conditions. The goal was to test the long-term treatment efficiency and identify inhibitory factors. The highest COD removal of up to 97% was observed when the influent concentration was increased by the addition of methanol (up to 25gL-1 as COD). Varying and generally lower COD removal efficiency (around 78%) was observed when the anaerobic membrane bioreactor was operated with incoming pharmaceutical wastewater as sole carbon source. The addition of waste organic solvents (>2.5gL-1 as COD) to the influent led to low COD removal efficiency or even to the breakdown of anaerobic digestion. Changes in the anaerobic population (e.g., proliferation of the genus Methanosarcina) resulting from the composition of influent were observed.
Keywords: Pharmaceutical wastewater; anaerobióza; Anaerobiosis; měření biologické spotřeby kyslíku; Anaerobic membrane bioreactor (AnMBR); membrány umělé; Inhibition of methanogens; Fouling; Solvents; rozpouštědla; farmaceutický průmysl; Wastewater; pilotní projekty; Pilot Projects; Waste Disposal, Fluid; Biofuels; Carbon; průmyslový odpad; Waste Water; Biogas; Membranes, Artificial; COD removal; Industrial Waste; Bioreactors; odpad tekutý - odstraňování; odpadní voda; Drug Industry; biopaliva; uhlík; bioreaktory; Biological Oxygen Demand Analysis